Adult education and working women: A perspective on the life and work of Eva vom Hansl - Kimberly A. Townsend (Adult Education Research Conference, 1993)
This paper presents an historical review of working women from colonial times through World War II and links working women and adult education through the work of Eva vom Hansl.